2015
DOI: 10.1002/asi.23581
|View full text |Cite
|
Sign up to set email alerts
|

Sharing “happy” information

Abstract: This study focusses on the sharing of 'happy' information; information that creates a sense of happiness within the individual sharing the information. We explore the range of factors motivating and impacting upon individuals' happy information sharing behaviour within a casual leisure context through 30 semi-structured interviews. The findings reveal that the factors influencing individuals' happy information sharing behaviour are numerous, and impact upon each other. Most individuals considered sharing happy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Research on information access, seeking, and representation in leisure settings, migration, healthcare, and the home has expanded information science beyond contexts such as schools and libraries, which continue to be focal points in the field (Allard 2015;Cox and Blake 2011;Dali 2013;Given et al 2016;Gorichanaz 2015;Hartel 2010;Lloyd 2014a;Loudon, Buchanan, and Ruthven 2016;McKenzie 2010;Quirke 2015;Tinto and Ruthven 2016;Huvila 2013;Lloyd 2009;Molopyane and Fourie 2015;Pilerot 2016;Takhteyev 2012). Although religious practice is another important part of everyday life (refer to, e.g., Statistics Canada 2013), with the exception of a small number of studies on information seeking and use among Christian clergy (e.g., Michels 2014;Roland 2012;Roland and Wicks 2009), research about the role of information in religious practice remains marginal.…”
Section: Introductionmentioning
confidence: 99%
“…Research on information access, seeking, and representation in leisure settings, migration, healthcare, and the home has expanded information science beyond contexts such as schools and libraries, which continue to be focal points in the field (Allard 2015;Cox and Blake 2011;Dali 2013;Given et al 2016;Gorichanaz 2015;Hartel 2010;Lloyd 2014a;Loudon, Buchanan, and Ruthven 2016;McKenzie 2010;Quirke 2015;Tinto and Ruthven 2016;Huvila 2013;Lloyd 2009;Molopyane and Fourie 2015;Pilerot 2016;Takhteyev 2012). Although religious practice is another important part of everyday life (refer to, e.g., Statistics Canada 2013), with the exception of a small number of studies on information seeking and use among Christian clergy (e.g., Michels 2014;Roland 2012;Roland and Wicks 2009), research about the role of information in religious practice remains marginal.…”
Section: Introductionmentioning
confidence: 99%
“…As in experimental settings, experiencing gratitude was reported to encourage future prosocial behavior among both beneficiaries and benefactors (McCullough et al, ), and among other community members through third‐party influence (Layous et al, ). Motives were reported as seemingly altruistic, akin to “gift giving” (Tinto & Ruthven, ). However, several participants reported enjoying feeling socially rewarded (see Grant & Gino, ), with some expressing a clear desire for reward and increased social standing.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dantonio et al (2012) found social media users shared information they encountered serendipitously altruistically. Similarly, Tinto and Ruthven (2016) found sharers of "happy" information (information that evokes happiness within the sharer) gained pleasure from making others happy. They identified "giftgiving" as an important ritual, which did not depend on others' reactions to the giving.…”
Section: Altruism and Reciprocity In Online Communitiesmentioning
confidence: 98%
“…To speak of other outcomes of information, Sköld () presents a study of memory practices in an online gaming community, wherein people share screen captures from their game and associated stories as modes of reminiscing and constructing knowledge. Finally, Tinto and Ruthven () give an example regarding information sharing; they explored the methods and factors of sharing so‐called happy information (that is, that which creates a sense of happiness when shared). Alhough these practices are rooted in pleasure, which is at risk of being classified as mere hedonism, Tinto and Ruthven discuss how sharing happy information can enhance human relationships, and be shared with that intent, thus constituting deeper personal meaning than at first may appear.…”
Section: Personal Meaning and Information Behaviormentioning
confidence: 99%